1991
DOI: 10.1111/j.1440-1754.1991.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of hospitalization in extremely preterm infants

Abstract: This study reports the age at hospital discharge of 233 survivors and age at death of 209 infants who were born at 23-28 weeks gestation over a 10 year period, 1977-86. The mean duration of hospitalization of survivors was 95 days and was inversely related to maturity at birth; those born at 23-25 weeks remained in hospital on average 1-2 weeks beyond term while those born at 26-28 weeks went home on average at term or 1 week before term. The mean age at death was 12 days: 53% within 1 day, 23% between 2 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…19 The median gestational age at discharge home decreases with increasing gestational age at birth in New South Wales. This confirms the findings of Yu et al 40 in Victoria, Australia, in the 1980s.…”
Section: Discussionsupporting
confidence: 92%
“…19 The median gestational age at discharge home decreases with increasing gestational age at birth in New South Wales. This confirms the findings of Yu et al 40 in Victoria, Australia, in the 1980s.…”
Section: Discussionsupporting
confidence: 92%
“…7 The average duration of the length of stay of extremely premature babies (23-28 weeks of gestation) during 1977 to 1986 was 95 days and was inversely proportional to gestational age. 8 A recent large multicenter study of infants, born ≤28 weeks gestation and admitted to one of 12 tertiary US centers between January 1998 and October 2001 showed that 18% of infants had a prolonged length of stay defined as discharge at >42 weeks post-menstrual age. 4 An audit of hospital admissions to children's hospital groups in Ireland showed that of all infants that needed a hospital stay of >1 month, there were 4.4% (19/436) that needed a hospital stay of >6 months with an average stay of 331 days.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of hospital length of stay to mortality has shown that the majority of neonatal mortality is within the first 1-2 weeks of birth. 8,10 A study by Catlin et al using the KID 2003 data of 680 neonates who stayed ≥180 days reported a mortality rate of 16%. 1 In the present study, 812 neonates stayed for ≥180 days with a mortality rate of 10.9%.…”
Section: Discussionmentioning
confidence: 99%